2005
DOI: 10.1097/01.gco.0000162190.83972.5a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and fetal diagnosis

Abstract: Imaging techniques have been critical in the development of screening methods for Down syndrome or trisomy 18 and for euploid fetuses at high risk for adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 105 publications
0
11
0
2
Order By: Relevance
“…It is widely accepted that severe categories of VM are associated with higher risks of poor clinical outcome, 12 and indeed recent studies have questioned whether mild VM (trigone measurements of 10 -12 mm) is truly abnormal if it is an isolated finding. 13,14 For example, in a study of 176 cases, Gaglioti et al 7 showed that a fetus with isolated VM had a 97.7% chance of being alive at 2 years if the VM was mild, an 80% chance with moderate VM, and a 33.3% chance with severe VM. Of those that were alive, neurodevelopmental outcome was normal in 93% of mild cases, 75% of moderate, and 62.5% of severe VM cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that severe categories of VM are associated with higher risks of poor clinical outcome, 12 and indeed recent studies have questioned whether mild VM (trigone measurements of 10 -12 mm) is truly abnormal if it is an isolated finding. 13,14 For example, in a study of 176 cases, Gaglioti et al 7 showed that a fetus with isolated VM had a 97.7% chance of being alive at 2 years if the VM was mild, an 80% chance with moderate VM, and a 33.3% chance with severe VM. Of those that were alive, neurodevelopmental outcome was normal in 93% of mild cases, 75% of moderate, and 62.5% of severe VM cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies have been proposed in several ways: sequential testing, in which the gravida elects, after knowing the primary results, to add new markers [30,31] (quadruple screening and/or second trimester ultrasound markers such as short humerus, short femur, hydroncphrosis, echogenic cardiac foci, echogenic bowel, uterine arter>', etc. ); and contingency testing [32], in which additional screening is only performed for an intermediate-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for stratification of fetal distress to determine if and when intrauterine intervention is necessary. Doppler velocimetry, although not useful for identifying congenital heart defects, is helpful for the evaluation of fetal myocardial function (7). Venous velocimetry can be used to detect hydrops, an indicator of imminent demise due to high-output cardiac failure seen in arterio-venous shunts due to sacrococcygeal teratomas and other malformations (7).…”
Section: Imaging Modalitiesmentioning
confidence: 99%